The Inhibiting Factors Analysis of BIM Implementation in Jambi City’s Construction Companies - Azrita, Nada Milani; Hidayat, Benny; Ophiyandri, Taufika (Universitas Negeri Padang, 2024)
The development of information and communication technology is increasing every year, contruction sector indeed. The rapid increase in technology in the construction sector has forced all AEC actors in Indonesia to follow these developments as an effort to increase work productivity. The breakthrough that can support infrastructure development to follow the digitalization era is the use of various technologies and applications of Building Information Modeling (BIM) which have many benefits. However, for the implementation of BIM in Jambi City itself still relatively low, from the maturity level of BIM based on the model (Succar, 2010) obtained a value of 0.719 at the non-existence level, which means that the use of BIM in construction companies in Jambi City has not yet been implemented. the discovery of the potential use of BIM, even seen from the optimism of the implementation of BIM in the company, not all informants have high optimism. Therefore, a study was conducted on the inhibiting factors that hindered the implementation of BIM in construction companies in Jambi City, using interview techniques to determine the actual obstacles. The 5 highest barriers factors were identified, that is Lack of understanding of BIM and its benefits, Lack of government support, Requires high hardware specifications, High investment costs for BIM official licenses, Lack of market demand (Clients). With this research, it is hoped that the application of BIM can be better and provide maximum benefits to construction companies in Jambi City.